IMPORTANT FINDINGS OF DISTRIBUTION OF CERAMICS IN LAMREH AND UJONG PANCU, ACEH - Jovial Pally Taran (The Department of Islamic History and Culture in cooperation with the Center for Research and Community Service, Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2021)
Research by the Aceh Geohazard Project (AGP) at the International Center for Aceh and Indian Ocean Studies (ICAIOS), in collaboration with the Earth Observatory of Singapore (EOS), in 2015-2017, showed that there was an important distribution of ceramic fragment artifacts along the coast. the coast of Aceh, especially in the Bukit Lamreh area to the coast of Ujong Pancu. The method used in this study is in the form of observation and recording of archaeological data by recording each type of ceramic shard artifact finding from the type of material and form and art style, then recording with photography and analysis of the findings. The ceramic shards found in Lamreh Hill are dominated by Chinese green ceramics, and the rest comes from ceramics produced by Thailand, Burma, Vietnam, India and Syria. Most of these findings are ceramics from the early 13th century AD to the late 15th century AD. Meanwhile, on the coast of Ujong Pancu, variations of ceramics dominated by China were found from the period 12-19 AD, although various types of ceramics were also found from Thailand, Vietnam, Japan, Burma, even Europe. The discovery of the distribution of ceramics in these two important locations indicates a significant maritime route activity between Aceh and several other kingdoms, especially the Chinese dynasty. This proves that Aceh already has its own civilization even since 1000 years ago, through the discovery of the ceramic shards.